Work Life Balance and Work Stress on Turnover Intention Mediated Job Satisfaction - Septiana Arum Sari; Esti Margiyanti Utami; Fitri Rahmawati (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze work-life balance and job stress on turnover intention of Generation Z employees, with job satisfaction serving as a mediating variable. This study uses a quantitative methodology with a survey method.” Generation Z employees in the service sector in Purworejo Regency were surveyed using a questionnaire, and the data were evaluated using statistical methods. In contrast to work stress, which has a positive effect on turnover intention but a negative effect on job satisfaction, work-life balance has a positive effect on both turnover intention and job satisfaction, according to the study's results. The association between work-life balance and job stress on turnover intention is mediated by job satisfaction, which has been found to have a negative effect on turnover intention. The study's conclusions indicate that improving work-life balance and managing stress are crucial for increasing job satisfaction and reducing Generation Z employees' desire to change jobs.